Antiobiotic resistance in the current realities of cardiac surgery - Lazoryshynetz, V. V.; Spysarenko, S. P.; Krykunov, A. A.; Malysheva, T. A. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Today microbial resistance to current antibacterial agents is constantly growing. A significant increase in the role of nosocomial factors in patients with primary infection has a negative impact on the results of cardiac surgery. Materials and methods. The basis of the study is clinical data of 2992 patients, operated on at SI «National Amosov Institute of Cardiovascular Surgery» NAMS of Ukraine from 01.01.2004 to 01.12.2015 yy. The main nosological forms were: infective endocarditis – 2603 (87.0%) patients, sepsis – 132 (4.4%) and patients with bacteremia – 257 (8.6%) patients. Results and discussion. The rate of pathogen identification was 1497 (50.03%) cases. Gram-positive microflora was identified in 1001 (66.9%) cases, gram-negative pathogens were reported in 359 (24.0%) cases. Fungal flora quotient was 137 (9.1%) cases. The number of resistant strains to antibiotics of reserve group – vancomycin and linezolid - reached 64.3% and 34.2% of cases respectively. In 2015 the proportion of resistant strains to colomycin and fosfomycin reached 65.3% and 44.0% respectively. Over the observed period septic diseases caused by combination of ESKAPE group pathogens and fungal microflora, accompanied by severe organ lesions, were found. Conclusions. For overcoming antibiotic resistance it was offered: the use of total body controlled hyperthermic perfusion intraoperatively in patients with infective endocarditis; combination of passive immunization and antibiotic therapy; the use of drugs violating the intercellular communication of bacteria.